Immunophenotypic Analysis in Early Müllerian Serous Carcinogenesis. (September 2015) - Nafisi, Houman; Ghorab, Zeina; Ismill, Nadia; Dubé, Valerie; Plotkin, Anna; Han, Guangming; Cesari, Matthew; Lu, Fang-I; Saad, Reda; Khalifa, Mahmoud; Nofech-Mozes, Sharon
Abstract : Studies on the immunophenotypes of early forms of serous carcinoma arising from female genital tract are limited. We aimed to examine p53, p16 Ink4a, estrogen receptor (ER), progesterone receptor (PR), ERBB2, WT1, and Ki-67 protein expression in endometrial intraepithelial carcinoma (n=29), serous tubal intraepithelial lesion (n=4) and carcinoma (STIC, n=10), and the putative precursor p53 signature (n=11). Among endometrial intraepithelial carcinoma, 80% demonstrated p53 overexpression and 10% were consistent with a null phenotype. p16 Ink4a immunostaining were observed in all endometrial intraepithelial carcinoma cases. ER, PR, ERBB2, and WT1 were positive in 54%, 25%, 11%, and 18% of cases, respectively. STIC cases demonstrated p53 overexpression and null phenotype in 90% and 10%, respectively. All STIC cases were p16 Ink4a and WT1 positive, whereas ER and PR were positive in 70% and 20%, respectively. All STICs were negative for ERBB2. Among serous tubal intraepithelial lesion cases, 75% demonstrated p53 overexpression and 25% a null phenotype. p53 was positive in all 11 p53 signature cases, whereas p16 Ink4a was universally negative. Finally, ER and PR were positive in 100% and 73% of p53 signature cases, respectively. These results suggest that p16 Ink4a has a role in early Müllerian serous carcinogenesis but is absent in the earliest noncommitted lesion. p16 Ink4a immunohistochemistry can be used as an adjunct confirmatory tool in p53-null cases with limited surface area.